TRANSFORMASI: : KAJIAN HISTORIS-TEOLOGIS TENTANG PENGARUH AJARAN KRISTUS BAGI PERADABAN DUNIA - Baitanu, Victor (Jurnal Teologi RAI, 2024)
Transformation means change in relation to what Jesus Christ did. According to some theologians, Jesus lived in Palestine in the context of slavery at that time, but there is no information that Jesus forbade slavery. For this reason, the author examines using a historical study approach to provide answers to these problems. In this study, the authors find that slavery during the time of Jesus' ministry was not as understood by the world in today's context because slavery at that time was one of the options for survival. Slavery, cruelty, murder, abortion, end when the seed of the gospel is sown and that is what changes the human heart to love. There are many transformations that occur due to the influence of Christ's teachings, such as the social status of women before and after Jesus and so on. This research aims to convey to the world about the transformation that occurs due to the influence of the teachings of Jesus Christ that change everyone's hearts to love one another as fellow bearers of God's image and only with such awareness will bring people to one point of view that all people are valuable in God's eyes and When that consciousness is present in every human life then the act of theft, Robbery, murder and various crimes will come to an end. It is the teachings of Jesus Christ that can bring about this kind of transformation.